The effectiveness of bovine tuberculosis surveillance in Dutch badgers. Issue 4 (12th July 2021) - Orrico, Mario; van Schaik, Gerdien; Koets, Ad; van den Broek, Jan; Montizaan, Margriet; La Haye, Maurice; Rijks, Jolianne M.
Abstract: Countries survey wildlife for bovine tuberculosis (bTB) to ensure case detection or to ascertain a high probability of freedom from bTB in wildlife. The Eurasian badger ( Meles meles ) is a potential bTB reservoir host. Between 2008 and 2019, 282 badgers were examined post‐mortem in the context of general wildlife disease and targeted bTB surveillance programmes in the Netherlands, and no bTB cases were detected. However, it was unclear how effective this surveillance effort was to demonstrate freedom from Mycobacterium bovis infection in the badger population of ±6000 or to detect cases if present. Therefore, surveillance effectiveness was assessed using scenario tree modelling. For lack of standards for wildlife, the models were run against three assumed levels of disease in the population called design prevalence P* : 0.1%, 0.5%, and 3%. A small risk of introduction (0.015/year) was applied, because the Netherlands are officially free from bTB in cattle, with rare import of bTB‐infected cattle and no bTB‐infected wildlife reported along the Belgian and German borders with the Netherlands. Surveillance more readily picks up bTB presence in badgers when case detection sensitivity tends towards 100% and demonstrates freedom best when the probability of freedom tends towards 100%. For P* 0.1%, 0.5% and 3%, respectively, maximum case detection sensitivity during 2008–2019 was 8%, 35% and 94% and the probability of freedom in 2019 was 46%, 67%, and 95%. At P*  = 3%, performing targeted surveillance on 300 badgers in a year would make it extremely unlikely to miss a case (case detection sensitivity > 99.9%); and if no cases are detected, the adjusted probability of freedom would then reach nearly 98.5%. Stakeholders should be made aware that at P*  = 3%, one case detected implies around 3% infected badgers. Additional surveillance system components to assess bTB in wildlife and its economics are to be explored further.